Synthesis and SAR Evaluation of Mercapto Triazolobenzothiazole Derivatives as Anti-tuberculosis Agents - S.V, Mamatha; Belagali, S.L.; Bhat, Mahesh (Anti-Infective Agents, 2020)
Background: Benzothiazoles possess a vast sphere of biological activities including anti- inflammatory, antibacterial activities whereas triazoles display various pharmacological properties including antimicrobial and antitubercular activities. Hence, triazole conjugated benzothiazole side-chain anticipating their interesting biological properties has been focused upon. Objective: The objective of the current work is synthesis and biological evaluation of a new series of benzothiazole appended triazole derivatives. Methods: The target compounds were prepared via a multi-step method involving the treatment of 2-amino benzothiazole with hydrazine followed by cyclization with carbon disulfide to give the corresponding triazol-2-thiol derivatives and then alkylation of these derivatives. All the synthesized compounds were characterized by FT-IR, Mass, 1;H and 13C NMR spectra and were screened for their antibacterial, antioxidant, anti-inflammatory and anti-tubercular (anti-TB) activities in vitro. These molecules were also docked into the enoyl acyl carrier reductase (Inha, PDB ID-1ZID) in silico. Results: While all the synthesized compounds were active against M. tuberculosis at 50 μg/ml, the pyrrolidine and piperidine appended benzothiazolyltriazoles showed the superior activity (MIC values 12.5 to 1.6 μg/ml). Compound 5a (5-CH3 with piperidine), 5b (7-CH3 with piperidine) and 7b (7-CH3 with pyrrolidine) showed good antibacterial activity against Staphylococcus aureus with MIC value 31.25μ g/ml, while compounds 7a (5-CH3 with pyrrolidine), 6b (7-CH3 with morpholine) and 8c (7-Br with pyridine) exhibited good antibacterial activity against E-coli with MIC value 62.5μg/ml. Compounds 7b (7-CH3 with pyrrolidine) and 5c (7-Br with piperidine) showed good anti-oxidant activities with IC50 values 93.25 and 82.25, respectively. Notably, these compounds were non-toxic to the normal cells even at high concentrations with IC50 value 238μg/ml. Conclusion: The compound 7b, a benzothiazolyltriazole having a pyrrolidine group (five membered ring) attached to two CH2 groups and methyl substituent at 7th position of the benzothiazole ring emerged as a novel and promising hit molecule that showed anti-TB, antimicrobial and antiinflammatory activities in vitro.
Keywords: in silico